The Philosophy of Ch'eng I - Ts'ai, Yung-ch'un (China Academic Library,, 2018)
This book offers a comprehensive account of the great Neo-Confucian Master Cheng I (1033-1107), showing his philosophical ideas in a modern light. It systematically examines Cheng's extensive literature and provides an ingenious interpretation of Cheng's social and political views. The author, Yung-ch'un Ts'ai, was a respected scholar of sociology and theology in 20th century China. .